Sensitivity to reward, food addiction and obesity in mothers and children - Santos-Flores, Jesús Melchor (Universidad de Sonora, 2021)
Introduction: Overweight and obesity are considered an epidemic that affects the population of all ages. The characteristics present in the mother and school age children dyads such as sensitivity to the reward upon eating in excess and the addiction to food can be potential regulators of body weight. Objective: Understand the influence of sensitivity to rewards, addiction to food and the maternal nutritional status in regard to sensitivity to rewards, addiction to food and nutritional status of children. Methodology: Descriptive-correlational design. Sample composed by 218 pairs. Weight and size were measured, applying a sociodemographic data card, as well as four measurement instruments. The data was captured and analyzed throughout SPSS. Results: 69.3% of the mothers were overweight and obese, and 27.9% of the children. They reported high sensitivity to reward (38.4 and 40.4), and mean higher in those overweight and obese (p < .001). 13.8% of mothers and 8.3% of the children presented addiction to food. Mothers and children with addiction to food showed a higher score of sensitivity to reward (p < .001). The body mass index, sensitivity to reward and addiction to food on the mothers’ behalf influenced the body mass index of the child (p < .005). Conclusions: These maternal characteristics would be present in children, they can increase according to age, persist into adult age and be transmitted towards their future children.